Analisis Kekerasan Terhadap Orang Lanjut Usia (Lansia) Perempuan di Indonesia - Melanie Pita Lestari; Fransiska Novita Eleanora; Zulkifli Ismail (University Of Bengkulu Law Journal, 2023)
The problem of violence against women in Indonesia is basically still a mystery that has not been fully resolved by either the government or social organizations concerned with the issue. Violence against women is one of the main problems in the study of Anthropology which also intersects with the studies of feminism, gender equality and gerontology. This problem actually does not only occur in Indonesia, but also throughout the world. At present, violence against women is considered a serious case in Indonesia, because until now these cases of violence are still occurring and even tend to increase and are more varied. Therefore, in this paper, we will discuss violence against elderly women in Indonesia. This study uses a normative juridical research method with a conceptual approach. The results of this study are that elderly women are considered more likely to be victims of violence than elderly men, because elderly women are considered weak, very dependent on other people, unproductive and a burden on the family. The forms of violence against the elderly in Indonesia include; Physical violence, Psychological violence or Emotional violence, Sexual violence, Financial exploitation and Neglect. Violence against elderly women in Indonesia itself is difficult to reveal because it is in the domestic realm of the household which is personal in nature. Keywords: violence, elderly, women